Jazz a regional exploration - Yanow, Scott; Gale Group (Westport, Conn. Greenwood Press, 2005)
Focuses on the music's development that resulted in different styles and approaches to jazz improvisation being created in different cities and areas of the country.
Sedalia and St. Louis : ragtime -- New Orleans jazz -- Chicago : classic jazz -- New York : the classic jazz and swing eras -- Kansas City swing, the territory bands, and the San Francisco revival -- New York bebop, Latin, and cool jazz -- Los Angeles : West Coast cool jazz -- New York : hard bop and soul jazz -- New York : free jazz and the avant-garde -- Chicago : the avant-garde -- New Orleans : the young lions -- Modern jazz : fusion and beyond.
Electronic reproduction.
Keywords: Jazz -- History and criticism; Electronic books